“Elaboración de un producto cárnico cocido tipo jamonada de pavo y cerdo, utilizando aceite de semilla de cáñamo (Cannabis sativa ssp) como aditivo de omega 3, 6.” - Grandes Veloz, Pablo Giovanni (2022)
The main objective of the proposed research is to produce a turkey and pork cooked meat product using hemp (Cannabis sativa ssp) seed oil, in order to accomplish the stated objectives, a randomized complete block design (RCBD) was developed, with a factorial arrangement A x B with factor A is percentages of turkey meat at three levels 50%, 33,33% and 66,66%; pork meat at three levels 50%, 66,66% and 33,33% (in a 1:1, 1:2, 2:1 relation), factor B is percentage of hemp seed oil, at two levels 153 g and 0 g; given the interactions on both factors, 6 treatments were obtained. In order to select the best of all the treatments, organoleptic (through a hedonic scale to find out the acceptability), which through the statistical software InfoStat the best treatment was determined, where the organoleptic characteristics (taste, texture, smell and flavor) were evaluated, obtaining as best result the (t6) (a3b2) treatment respectively, which have 2 Kg turkey meat; 1 Kg pork meat; with 153 g of hemp seed oil, improving the product through an adequate technological process. On which bromatological analysis were made where we have a protein result of 17,56 ± 0,34 %, ashes result at 4,67% and for the microbiological analysis results consequently we have the detection of Escherichia coli and total coliforms that gives us results of a minimum presence of <10 UFC/g and the detection of Salmonella spp shows absence of it, then a production cost analysis of the cooked meat Ham type product was carried out, considering fixed costs and variable costs, that resulted in a presentation of 200g with a retail cost of $6.92 with a profit of $ 2.96, being a competitive price in relation to other products in the market with similar characteristic.